New isoflavans from the root bark of Erythrina livingstoniana. (September 2016) - Bedane, Kibrom Gebreheiwot; Masesane, Ishmael B.; Majinda, Runner R.T.
Graphical abstract: Highlights: Two new isoflavans were isolated from the root bark of Erythrina livingstoniana . The structures were elucidated based on spectroscopic data. The absolute stereochemistry for the isolated isoflavans was determined by CD and optical rotation measurements. Isolation of different enantiomeric forms of isoflavans obtained from the same plant unusual and suggests some isolates may be impure. This is the first report on the root bark of the plant. Abstract: The phytochemical study on the root bark of Erythrina livingstoniana has led to the isolation of two new isoflavans namely 7-hydroxy-2′-methoxy-[6′′, 6′′-dimethylpyrano (2′′, 3′′:4′, 5′)]isoflavan (1 ) and 7, 2′-dihydroxy-[6′′, 6′′-dimethyl pyrano (2′′, 3′′:4′, 5′)]isoflavan (2 ) together with eight known flavonoids (3 -10 ). Their structures were elucidated on the basis of spectroscopic analyses (1D- and 2D-NMR and ESI-HRMS) and by comparison with literature data.